Afectividad y espacio biográfco en Centroamérica. Dos cartas de guerra y exilio - Carrillo Padilla, Ana Lorena (2017)
This article is part of a larger and broader research project in course. What is discussed here is the theoretical relevance of the affect studies or affectivity studies in a cultural framework for the analysis of autobiographical texts produced during the armed conﬂict in Central America during the 80's decade of the XX century. In the frst part of this text a general presentation of the themes of affect and biographical space is outlined. On the second part, a brief state of the art is presented as it relates to Central America with an emphasis on Guatemala. On the third and last part, two pieces of a small collection of family letters are analyzed. This is done within -a yet to be explored- Central American Biographical Space of the Armed Conﬂict as a mode or example as to how to approach and read/analyze this literature from diverse perspectives, one of them being that of affectivity.